Comparison of shivering incidence between post-surgery patients with general anesthesia and those with regional anesthesia at PKU Muhammadiyah Gamping Hospital - Yosy Budi Setiawan; Intan Sarah (Publikasi Indonesia, 2024)
Anesthesia is an action performed during surgery for total or regional pain relief. One of the complications that often occur after anesthesia is shivering. The impact of shivering will stretch the surgical wound and cause pain, complications of infection and bleeding. This study aims to compare the incidence of shivering between post-surgery patients with general anesthesia and those with regional anesthesia. Its primary data were collected from PKU Muhammadiyah Gamping Hospital by a consecutive sampling. The study was conducted by dividing 50 respondents into two groups; the post-surgery patients with general anesthesia were 20 respondents and those with regional anesthesia were 30 respondents. After examined with Mann Whitney’s SPSS, the incidence of shivering in the patients with general anesthesia was 10%, and those with regional anesthesia was 13.3%. The comparison of the incidence of shivering between both groups obtained a significance value of 0.725 > 0.05, and it could be concluded that there was no difference in the incidence of shivering in the patients with general anesthesia and those with regional anesthesia.